RSV glycoprotein and genomic RNA dynamics reveal filament assembly prior to the plasma membrane - Daryll Vanover (Nature Portfolio, 2017)
Assembly of filamentous RSV particles is incompletely understood due to a lack of techniques suitable for live-cell imaging. Here Vanover et al. use labeled soybean agglutinin to selectively label RSV G protein and show how filamentous RSV assembly, initiated in the cytoplasm, uses G protein recycled from the plasma membrane.